Improved Technology for Rounding Graphite: Machine Structure and Industrial Test - Jundong Chen; Tingting Ma; Yan Lu; Jianbo Wang; Mingxing Zhang; Longyuan Lin; Cuiping Yan; Xue Li; Haiyan Chen (Applied Sciences, 2023)
The graphite, which is treated to be potato-shaped, is widely applied in Li-ion batteries as the anodic material. Sequential batch shaping is the main method at present. However, the small height of the shaping cavity of the existing structure leads to the problem of low processing capacity and high cost. In this work, a new structure of the shaping machine was developed with the aim of shaping graphite by large output and costless. The equipment system for graphite rounding in a pilot scale at a treatment amount of 25 kg raw material each run was established. The results showed that the ratio of the diameters of the final product by an undersized percentage corresponding to 10% was 11.15 μm, 50% was 18.94 μm, and 90% was 29.54 μm, and tap density was 0.945 g/cm3, the yield reached 48%, under the optimized conditions of 1833 rpm rotating speed of shaping disk, 2646 rpm rotating speed of classifier, and 40 min shaping period. All the above characteristics of the rounded graphite are in line with the requirements for applying in the anode of Li-ion batteries. In short, the present study aims to provide a new structure of the shaping machine, contributing to the efficient and cost-effective rounding of graphite and revealing the structure of the shaping machine, contributing to promoting the wide improvement of the shaping machine.